Engineering Lifetime Model of Crosslinked Polyethylene under Electrical and Thermal Stresses - Sarawuth Pramualsingha; Peerawut Yutthagowith (My University, 2021)
This paper presents an effective engineering lifetime model of crosslinked polyethylene (XLPE), which was subjected to electrical field stresses in the range of 7 to 90 kV/mm and temperatures of 20 to 90 °C.The inversed power model (IPM) is widely used for estimating the lifetime of XLPE under the influence of high electrical field stress at a constant operating temperature or under an accelerating aging test.However, it was previously found that the IPM is not appropriate when XLPE is subjected to both low electrical and thermal stresses, which is similar to the actual conditions of power cables installed in electrical power transmission systems.From the experimental results of the lifetime of XLPE under electrical field stresses at specific temperatures, an inflection point was found at a certain electrical field stress (E d ).From this observation and based on a physical interpretation, an engineering lifetime model was derived by separation of the lifetime curve into two parts, i.e., for electrical field stresses of lower than E d and higher than E d .Nonlinear and linear least-squares methods were applied to fit the developed model with the experimental data, and the parameters of the developed engineering lifetime model were determined.With the developed model, the maximum electrical field stress at the maximum operating temperature can be determined, and it was utilized as a criterion in the design of power cables as an example in this study.
Keywords: Smart Materials for Construction